Program evaluation in practice : core concepts and examples for discussion and analysis - Spaulding, Dean T. (Research methods for the social sciences., 2014)
An udpated guide to the core concepts of program evaluation This updated edition of Program Evaluation in Practice covers the core concepts of program evaluation and uses case studies to touch on real-world issues that arise when conducting an evaluation project. This important resource is filled with illustrative examples written in accessible terms and provides a wide variety of evaluation projects that can be used for discussion, analysis, and reflection. The book addresses foundations and theories of evaluation, tools and methods for collecting data, writing of reports, and.